PERSEPSI PELANGGAN TERHADAP KUALITAS PELAYANAN PUBLIK PERUSAHAAN LISTRIK NEGARA (PLN) UNIT PELAYANAN DAN JARINGAN (UPJ) BEKASI KOTA - Dessianyanthi, Dahlia; Hubeis, Aida Vitayala S. (Jurnal Penyuluhan, 2016)
Public service is one form of the state apparatus functions as a public servant as well as aservant of the state. Seeing an increasingly competitive business world today, the company thatprovide public service need to change their customer services into a profit center. The quality ofservice provides an important link between the company and customers, also can help to push thecompany to achieve their goals and give positive image. Company's image depends on how thecompany give their services to the customer. Companies are required to constantly monitor publicperceptions or opinions about the company, through its institutional functions of Public Relation (PR).The purpose of this research is to analyze the customer's perception of the quality of public services atPLN UPJ Bekasi Kota, and the relationship between the internal and external factors with thecustomer's perception of public services at PLN UPJ Bekasi Kota. The results of this research showthe customer’s perception on the quality of public services at PLN UPJ Bekasi Kota is good with theaverage score equal to 3.86. Correlation test showed that there are five significant correlation, whichis the relationship between education level and assurance, education level and responsiveness,education level and tangibles, income level and tangibles, and the frequency of respondents callingand responsiveness.Keywords: Public Service, Quality of Service, PLN